PECULIARITIES OF LAND MANAGEMENT DURING MARITAL STATE IN UKRAINE: CHALLENGES AND SOLUTION WAYS - Дубовик, Іван (SWorldJournal, 2024)
The article examines the peculiarities of land management in the conditions of martial law in Ukraine. In particular, the article analyzes the challenges and problems that arise in the process of land management during military operations, such as the ina